Social media: An opportunity to reduce hookah smoke during an outbreak of COVID-19 - Saeed Bashirian; Elahe Ezati (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2021)
The tobacco epidemic is one of the biggest public health warnings in the world, and 8 million people die every year due to smoking, of which 7 million die due to direct smoking and 2.1 million due to exposure to secondhand smoke [1]. Hookah is a common and traditional way of smoking, which unfortunately has now become a fun and entertaining method, especially among teenagers, in today›s societies, especially in the Middle East. Smoking hookah at an early age and increasing its popularity among adolescents is a concern and an alarm [2].